Study on the Mechanism of Baimai Ointment in the Treatment of Osteoarthritis Based on Network Pharmacology and Molecular Docking with Experimental Verification - Zhu, Yingyin; Zhong, Wanling; Peng, Jing; Wu, Huichao; Du, Shouying (Frontiers in Genetics, 2021)
Purpose: The external preparation of Tibetan medicine formula, Baimai ointment (BMO), has great therapeutic effects on osteoarthritis (OA). However, its molecular mechanism remains almost elusive. Here, a comprehensive strategy combining network pharmacology, molecular docking with pharmacological experiments was adopted to reveal the molecular mechanism of BMO against OA. Methods: Traditional Chinese Medicines for Systems Pharmacology Database and Analysis Platform (TCMSP), Traditional Chinese Medicine Integrated Database (TCMID), GeneCards and DisGeNET database were used to screen the active components and targets of BMO in treating OA. Build Component-Target (C-T) network with the help of Cytoscape, and analyze the Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment through STRING. Autodock Tools was used to dock the key components and key target proteins. Animal experiments were performed to verify the key targets of BMO. Hematoxylin-eosin (HE) and Toluidine blue staining were used to observe the pathology of joints. Protein expression was determined using Enzyme-linked immunosorbent assay (ELISA). Results: Bioactive compounds and targets of BMO and OA were screened. The network analysis revealed that 17-β-estradiol, curcumin, licochalone A, quercetin and glycyrrhizic acid were key components, and IL6, TNF, MAPK1, VEGFA, CXCL8 and IL1B were key targets in treating OA. The KEGG indicated that TNF signaling pathway, NF-κB signaling pathway and HIF-1 signaling pathway were the main pathways. Molecular docking implied a strong combination between key components and key targets. The pathology and animal experiments showed BMO had great effects on OA via regulating IL6, TNF, MAPK1, VEGFA, CXCL8 and IL1B targets. Those findings were consistent with the results obtained from the network pharmacology approach. Conclusion: This study thoroughly illustrated the key components, key targets, and potential pathways of BMO against OA. It also provided a promising method to study Tibetan medicine formula or external preparations.